El Excentrico, 1961-03-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 20, 1961 [20 de marzo de 1961]. Ano 11, No 11. Cover has picture of six men dressed as well-known celebrities in 1960, with headline "Club Bachelors Interpretations of 1961 personalities."